2022
DOI: 10.1097/jsa.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications in Sports Surgery: Diagnosis and Management

Abstract: Orthopedic sports surgery of the knee and shoulder is generally considered to be safe and effective. Vascular complications can occur during or after arthroscopy of either joint. A thorough understanding of anatomy, particularly when placing portals in non-routine locations, is extremely important. Prompt recognition of any vascular complication is of significant importance. This review will discuss the potential vascular complications for both knee and shoulder sports surgery, review the relevant anatomy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 125 publications
(330 reference statements)
0
2
0
Order By: Relevance
“…A recent meta-analysis reviewing clinical outcomes after pediatric ACLR between 1985 and 2016 reported that 3.7% developed angular deformity and 7.5% had at least 1 cm of limb-length discrepancy, but no data were reported on neurovascular injuries. 44 While documentation of neurovascular damage during pediatric ACLR is scarce in the literature, 5 surgeons should be mindful that children have smaller distances between posterior knee neurovascular structures and surgical instrumentation used for extraosseous ITB graft passage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis reviewing clinical outcomes after pediatric ACLR between 1985 and 2016 reported that 3.7% developed angular deformity and 7.5% had at least 1 cm of limb-length discrepancy, but no data were reported on neurovascular injuries. 44 While documentation of neurovascular damage during pediatric ACLR is scarce in the literature, 5 surgeons should be mindful that children have smaller distances between posterior knee neurovascular structures and surgical instrumentation used for extraosseous ITB graft passage.…”
Section: Discussionmentioning
confidence: 99%
“…Neurovascular complications during knee procedures are rare but have been described for both pediatric and adult populations. 2 , 5 , 17 A 2015 literature review on pseudoaneurysms after arthroscopic knee procedures reported popliteal artery involvement in 46% of cases, with ACLR comprising 23% of reported cases. 10 Injuries to the popliteal artery specifically during the over-the-top approach for ACLR have further been reported.…”
mentioning
confidence: 99%